2020
DOI: 10.15241/jj.10.4.581
|View full text |Cite
|
Sign up to set email alerts
|

Recruiting, Retaining, and Supporting Students from Underrepresented Racial Minority Backgrounds in Doctoral Counselor Education

Abstract: Few models exist that inform how counselor education programs proactively address the gap between diverse student needs and effective support. In this study, we utilized grounded theory qualitative research to gain a better understanding of how 15 faculty members in doctoral counselor education and supervision programs reported that their departments responded to the need for recruiting, retaining, and supporting doctoral students from underrepresented racial minority backgrounds. We also explored participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…We propose these strategies might also be useful for dissertation chairs and students in the dissertation process to invite disclosure. Informed by the findings from this study and prior research (e.g., Ju et al, 2020), dissertation chairs should consider broaching cultural differences and cultural background with their doctoral students, invite conversations about their students' current and past educational experiences, and attend to possible concerns about future career opportunities. This discussion might also include the systemic concerns (e.g., microaggressions and harmful behaviors) that students have quietly endured in their educational experiences.…”
Section: Implications For Doctoral Students and Dissertation Chairsmentioning
confidence: 89%
See 1 more Smart Citation
“…We propose these strategies might also be useful for dissertation chairs and students in the dissertation process to invite disclosure. Informed by the findings from this study and prior research (e.g., Ju et al, 2020), dissertation chairs should consider broaching cultural differences and cultural background with their doctoral students, invite conversations about their students' current and past educational experiences, and attend to possible concerns about future career opportunities. This discussion might also include the systemic concerns (e.g., microaggressions and harmful behaviors) that students have quietly endured in their educational experiences.…”
Section: Implications For Doctoral Students and Dissertation Chairsmentioning
confidence: 89%
“…Counselor educators may also realize this need, as well. Ju et al (2020) interviewed counselor educators who engage with doctoral students on a regular basis in their program. These educators identified one essential component of support in the retention of students from underrepresented, racial minority backgrounds: the faculty's engagement with students on a personal and cultural level.…”
Section: Implications For Doctoral Students and Dissertation Chairsmentioning
confidence: 99%
“…HBCU graduates noted the extensive and personable mentoring while enrolled in the institution and after graduation. Ju et al (2020) underscored the significance of having a strategic approach to diverse mentoring students, as mentoring (formal and informal) allows authentic relationships to develop and thrive as students feel heard and "cared for." Our finding was also consistent with Joseph's (2007) study, which indicated that HBCU faculty are attuned to students' needs and provide mentoring focusing on degree advancement.…”
Section: Discussionmentioning
confidence: 99%
“…Participants noted a cluster of Black faculty who provided them with the "hidden curriculum" to navigate academia. Ju et al (2020) reinforced the concept of intentional mentoring as a strategy to support doctoral students of color by connecting them with faculty who can shepherd them through the doctoral process. Ju et al underscored the importance of routinely addressing the student's experiences.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are effective strategies that can be implemented to recruit doctoral students from these communities and increase their placement in IHEs. Systematic strategies may include addressing barriers to recruitment (e.g., such as standardized tests that measure aptitude and intelligence but reinforce negative stereotypes, expose inequities, and exclude capable ethnic minorities from doctoral study; Gómez et al, 2021; Randall, 2021; Woo et al, 2022), providing student-centered mentoring and advising (Santa-Ramirez, 2022), social support (Slay et al, 2019; Trent et al, 2021), funding (Hill & Conceição, 2020; Jones & Mandell, 2020; Merrell-James et al, 2020; Shealey, 2009), and transitional supports into the academy (Dieker et al, 2014). Using a tiered model to evaluate and identify supports for incoming students is another strategy that could increase access to the aptly termed “hidden curriculum” in doctoral studies (Felder & Barker, 2013).…”
Section: Shifting Our Lens: Social and Emotional Intervention Researc...mentioning
confidence: 99%